Silica micro/nanospheres for theranostics: from bimodal MRI and fluorescent imaging probes to cancer therapy - Walia, Shanka; Acharya, Amitabha (Beilstein Journal of Nanotechnology, 2015)
Nano-theranostics offer remarkable potential for future biomedical technology with simultaneous applications for diagnosis and therapy of disease sites. Through smart and careful chemical modifications of the nanoparticle surface, these can be converted to multifunctional tiny objects which in turn can be used as vehicle for delivering multimodal imaging agents and therapeutic material to specific target sites in vivo. In this sense, bimodal imaging probes that simultaneously enable magnetic resonance imaging and fluorescence imaging have gained tremendous attention because disease sites can be characterized quick and precisely through synergistic multimodal imaging. But such hybrid nanocomposite materials have limitations such as low chemical stability (magnetic component) and harsh cytotoxic effects (fluorescent component) and, hence, require a biocompatible protecting agent. Silica micro/nanospheres have shown promise as protecting agent due to the high stability and low toxicity. This review will cover a full description of MRI-active and fluorescent multifunctional silica micro/nanospheres including the design of the probe, different characterization methods and their application in imaging and treatment in cancer.
Keywords: bimodal imaging; fluorescence imaging; magnetic nanoparticles; organic dyes; quantum dots; silica nanospheres; theranostics